2017
DOI: 10.1007/s10856-017-5864-0
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of a novel abluminal groove-filled biodegradable polymer sirolimus-eluting stent

Abstract: Late stent thrombosis (LST) following drug-eluting stent (DES) implantation in patients with coronary artery disease (CAD) is often associated with delayed vascular healing, resulting from vascular inflammation and hypersensitivity to durable polymers and drugs. Therefore, DES design, materials, and coatings have been technologically revolutionized. Herein, we designed a novel abluminal groove-filled biodegradable polymer sirolimus-eluting stent (AGF-BP-SES), with a sirolimus content of only about one-third of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Prior studies have demonstrated delivery of sirolimus to the coronary artery in a controlled way with abluminal drug delivery. 10,11 The stent preserved a safe and effective local drug concentration without significant toxicity. Sirolimus-eluting stents have been used for reopening occluded Blalock-Taussig shunts in infants.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated delivery of sirolimus to the coronary artery in a controlled way with abluminal drug delivery. 10,11 The stent preserved a safe and effective local drug concentration without significant toxicity. Sirolimus-eluting stents have been used for reopening occluded Blalock-Taussig shunts in infants.…”
Section: Discussionmentioning
confidence: 99%
“…In a subgroup analysis, there were no signifi cant between-group diff erences with respect to prespecifi ed clinical and lesion characteristics. 10 Th e TAR-GET All-Comers study clearly demonstrated that the Firehawk stent is non-inferior to the benchmark XIENCE stent as assessed with the primary endpoint of TLF at 12 months in an all-comers population. Furthermore, the results confi rmed the clinical evaluations performed in China, and represent a successful global approval pathway for a Chinese DES in Europe.…”
Section: Clinical Evidencementioning
confidence: 97%
“…Th e Firehawk stent is designed to minimize polymer burden and reduce drug concentrations in the vessel wall. In fact, it represents the lowest polymer volume and drug concentration among currently available biodegradable polymer DES 10 . In a porcine model, the use of abluminal grooves allowed an equivalent concentration of sirolimus to be delivered to the endothelial tissue while decreasing the amount of circulating drug by nearly 7-fold when compared to the conventional Cypher sirolimus-eluting stent (Johnson & Johnson, New Brunswick, USA) (113 pg/ml vs. 733 pg/ml) 11 .…”
Section: Stent Design and Concept Of The Firehawkmentioning
confidence: 99%
See 1 more Smart Citation